Visualising scales of process: Multi-scalar geoarchaeological investigations of microstratigraphy and diagenesis at hominin bearing sites in South African karst. (July 2017) - Edwards, Tara; Grono, Elle; Herries, Andy I.R.; Brink, Frank J.; Troitzsch, Ulrike; Senden, Tim; Turner, Michael; Barron, Aleese; Prossor, Lauren; Denham, Tim
Abstract: Multi-scalar geoarchaeological investigations were conducted on several samples of sediment (dolomite cave sediments, ferricrete ridge, speleothem, tufa and tufa cave sediments) from four early hominin fossil-bearing sites (Taung Type Site, Haasgat, Drimolen Main Quarry, Elandsfontein) in different South African karst environments. The study was designed to test the value of geoarchaeological techniques for identifying and characterising environments of deposition and diagenetic processes involved in site formation within different mediums and different karst environments. The traditional petrographic method is weighed against two relatively new methodological contributions to site formation and diagenesis: Computed Tomography (CT) and automated Quantitative Evaluation of Minerals using Energy Dispersive Spectroscopy (QEM-EDS), employing QEMSCAN ® technology. An integrated micro-sampling approach is outlined for successful cross-correlation between techniques. The study demonstrates that different analyses vary in their ability to visualise different types of process – primary and secondary. Thin section petrography remains the 'gold standard' for analyses conducted at the micro-scale, while QEM-EDS and CT offer exciting potential to perform meso-scale analyses and are best utilised as complementary rather than alternative techniques to petrography. Highlights: A mixed-method geoarchaeological study of hominin-bearing sites in South Africa. Four sites in karst of different type, antiquity and genesis are studied. Thin section petrography, QEM-EDS and CT analyses are undertaken. Samples vary from well-stratified to well-homogenised. Processes of formation are visualised through complementary techniques.